Health-related decision making in two rural communities determinants and processes - Beray, Eunice I.
Families, at different stages in their life cycle, are confronted with various concerns where decision making is crucial. Among families with preschool children, health-related concerns press heavily on family resources, influencing decision making behavior, and consequently, the family's welfare. What, when and how the family decides when a preschooler is ill depends on the child, who is the object of the decision; the household, who provides the health-facilitating resources; the "gatekeeper" who controls family resources; and the community whose resources, prevailing beliefs and practices influence cognition, attitudes and behavior of individuals. The influence of these factors on content of decisions, process and decision makers in decision making was ascertained through conversational interviews of 85 mothers randomly selected from among those with preschoolers in two rural communities in Leyte. Findings of the study revealed that traditional medical practices were often sought and the wife was the frequent decision maker. Decisions with respect to what and when courses of actions were taken and how these were decide were influenced by how decision makers understood the health condition, their past experience and what they thought appropriate to do within the limits of their marginal economic condition and the community's health resources. Often, a single course of action was decided and done to a health condition perceived as a health problem. Decisions were routinary and recurring. This study concluded that mothers are rational in their decisions and that in reality, there are various processes by which decisions are made depending on the situation and relevant factors.